The lasting Welcome to the edge-there's no way back - Gross, Philip (United Kingdom oxford university press, 2016)
The Lastling is an enthralling story of adventure and survival in the face of relentless wilderness and ruthless hunters. The story is about a girl named Paris, who is on a trek in the Himalayas with her uncle and her uncle's friends. On the way they come across a young Tibetan monk, Tahr, who reluctantly joins their party as his protector has died in an accident. As the trek progresses, Paris realizes the true reason for the journey - her uncle and his friends are a strange, gourmet dining club, dedicated to hunting down and eating the rarest possible animals. So when they discover a young yeti-like creature, who is very nearly human herself, Tahr convinces Paris that they have a duty to protect her, come what may.